Consulting to social entrepreneurship initiatives - using business skills to help solve social problems: the RUG initiative - Silva, Ana Alexandra Gonçalves Rebelo da (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics